2021
DOI: 10.1001/jamaoncol.2021.2049
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Neuronal Autoantibodies and Cognitive Impairment in Patients With Lung Cancer

Abstract: IMPORTANCE Paraneoplastic neurological syndromes are associated with neuronal autoantibodies, and some of these autoantibodies are associated with neuropsychological symptoms. The most common underlying tumor is lung cancer. The association of neuronal autoantibodies with cognitive deficits has not been systematically investigated in patients with small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC).OBJECTIVE To assess the frequency of neuronal autoantibodies in patients with lung cancer and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 31 publications
1
24
0
1
Order By: Relevance
“…The second important clinical point is that concurrent with identifying the brainstem lesion, our patient showed a rapid cognitive decline, primarily a deficit in object-naming ability. Bartels et al showed that a high proportion of patients with lung cancer (67.0%) had cognitive impairment, with a similar prevalence between patients with small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC) [ 18 ]. Here, we can assume the following two mechanisms of cognitive decline in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second important clinical point is that concurrent with identifying the brainstem lesion, our patient showed a rapid cognitive decline, primarily a deficit in object-naming ability. Bartels et al showed that a high proportion of patients with lung cancer (67.0%) had cognitive impairment, with a similar prevalence between patients with small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC) [ 18 ]. Here, we can assume the following two mechanisms of cognitive decline in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…A second possible mechanism is that paraneoplastic anti-neuronal antibodies may lead to cognitive decline. Bartels et al reported that more than one-third of patients with lung cancer had neuronal autoantibodies that were found to be associated with cognitive decline [ 18 ]. We examined patient sera using a commercially available paraneoplastic neurological syndrome antibody panel and found no antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of brain-reactive autoantibodies was performed using c o m m e r c i a l a s s a y s ( a l l E U R O I M M U N M e d i z i n i s c h e Labordiagnostika AG, Germany) including cell-based assays (CBA) and immunohistochemistry (IHC) of frozen brain tissue (rat hippocampus, rat cerebellum, and monkey cerebellum). To that end, indirect immunofluorescence using BIOCHIP mosaics ™ was performed as described previously (24). To confirm CBA or IHC results for intracellular antigens, immunoblot assays (EUROLINE) were additionally performed.…”
Section: Neuronal Autoantibody Testingmentioning
confidence: 99%
“…The presence of neuronal autoantibodies is associated with neuropsychological syndromes and cognitive impairment (Bartels et al, 2019(Bartels et al, , 2021. In a study conducted by Hansen et al, the application of methylprednisolone immunotherapy was assessed in patients with neural autoantibodies.…”
Section: Editorial On the Research Topic Insights In Neuroinflammatio...mentioning
confidence: 99%